Mathematical Modeling in Combining Photovoltaic and Thermoelectric Generator Using a Spectrum Splitter - Hariyanto Hariyanto; Mustofa Mustofa; Zuryati Djafar; Wahyu H. Piarah (EPI International Journal of Engineering, 2019)
The experimental stages of converting solar energy into electrical energy in Photovoltaic and Thermoelectric Generator (PV-TEG) hybird ​​takes a long time. Modeling is one approach to find out the initial data before conducting experiments leading to minimize design errors, time and budget. A mathematical model is created to analyze the performance of a PV-TEG hybrid module. Modeling is performed as an electrical circuit equivalent to Kirchoff's Curent Law (KCL) by deriving several equations corresponding to the characteristics of each module. Type of PV is amorphous Silicon (a-Si), while TEG is Bismuth Telluride (Bi2Te3). The AM1.5D standard solar spectrum is splitted its wavelength spectrum using hot mirror, where the wavelengths of 400-690 nm are transmitted to PV and 690-1150 nm are reflected to TEG. All of PV-TEG hybrid parameters, for example intensity, temperature, and material property are obtained from the specification data of each module. As a results, the maximum total power is 0.0437 W with 5.1% its efficiency.